MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA KARTU HURUF PADA ANAK USIA 5-6 TAHUN DI TK WAHIDIN BAGANSIAPIAPI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Widarti, Widarti; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this research is still low ability to read the beginning of children in children aged 5-6 years at Tk Wahidin Bagansiapiapi District of Bangko Rokan Hilir. Necessary efforts to improve children's reading skills beginning. Efforts author of the letter through the media card. The purpose of this study was to determine whether there is an increase in reading skills of children through the media card beginning of this letter and to find out how high the increase that occurred. This research is a classroom action research. This research was conducted in two cycles and each cycle consisting of three meetings. Data collection tool used in this study is in the form of observation sheet. The number of samples in this study were 20 children consisting of 8 boys and 12 girls, a study conducted in kindergarten Wahidin Bagansiapiapi. Analysis of the assessment process there was an increase of 2 cycles beginning reading skills in children. A spike of observations before action to the first cycle of 29.28%, the first cycle to the second cycle of 45.12%, and increased from the prior cycle to cycle II of 87.62%. From these results it can be concluded that through the media card may improve the ability to read letters beginning in children aged 5-6 years in kindergarten Wahidin Bagansiapiapi District of Bangko Rokan Hilir.Keywords: The ability to read the beginning of the letter card